Determination of the dissociation constants for Ca2+ and calmodulin from the plasma membrane Ca2+ pump by a lipid probe that senses membrane domain changes - Mangialavori, Irene Cecilia (2010)
The purpose of this work was to obtain information about conformational changes of the plasma membrane Ca2+-pump (PMCA) in the membrane region upon interaction with Ca2+, calmodulin (CaM) and acidic phospholipids. To this end, we have quantified labeling of PMCA with the photoactivatable phosphatidylcholine analog [125I]TID-PC/16, measuring the shift of conformation E2 to the auto-inhibited conformation E1I and to the activated E1A state, titrating the effect of Ca2+ under different conditions. Using a similar approach, we also determined the CaM-PMCA dissociation constant. The results indicate that the PMCA possesses a high affinity site for Ca2+ regardless of the presence or absence of activators. Modulation of pump activity is exerted through the C-terminal domain, which induces an apparent auto-inhibited conformation for Ca2+ transport but does not modify the affinity for Ca2+ at the transmembrane domain. The C-terminal domain is affected by CaM and CaM-like treatments driving the auto-inhibited conformation E1I to the activated E1A conformation and thus modulating the transport of Ca2+. This is reflected in the different apparent constants for Ca2+ in the absence of CaM (calculated by Ca2+-ATPase activity) that sharply contrast with the lack of variation of the affinity for the Ca2+ site at equilibrium. This is the first time that equilibrium constants for the dissociation of Ca2+ and CaM ligands from PMCA complexes are measured through the change of transmembrane conformations of the pump. The data further suggest that the transmembrane domain of the PMCA undergoes major rearrangements resulting in altered lipid accessibility upon Ca2+ binding and activation.